2017
DOI: 10.24099/vet.arhiv.160412
|View full text |Cite
|
Sign up to set email alerts
|

Breed, gender, age and reproductive status in relation to the predisposition for cranial cruciate ligament rupture in 117 dogs treated by a single surgeon (2010 - 2015) - a short communication

Abstract: rupture of the cranial cruciate ligament (CCL) remains the most common canine orthopaedic problem seen in clinical practice. the present paper describes a population of 117 dogs with CCL rupture diagnosed by clinical examination followed by mini-arthrotomy. the dogs were treated from January 2010 to February 2015 at the Clinic for Surgery, Orthopaedics and Ophthalmology, Faculty of Veterinary Medicine, University of Zagreb, Croatia, by the same surgeon. The age, breed, gender and reproductive profile were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Breed has been extensively studied in relation to cranial cruciate ligament rupture and patellar luxation in dogs. 1,12,17,18,22,25,30,[32][33][34] In the current study, such asso-ciation was significant with both conditions, having groups 2, 3 and 8 higher odds of having cranial cruciate ligament rupture. According to previous reports, terrier breeds have increased risk for cranial cruciate ligament rupture.…”
Section: Veterinary and Comparative Orthopaedics And Traumatologymentioning
confidence: 73%
See 2 more Smart Citations
“…Breed has been extensively studied in relation to cranial cruciate ligament rupture and patellar luxation in dogs. 1,12,17,18,22,25,30,[32][33][34] In the current study, such asso-ciation was significant with both conditions, having groups 2, 3 and 8 higher odds of having cranial cruciate ligament rupture. According to previous reports, terrier breeds have increased risk for cranial cruciate ligament rupture.…”
Section: Veterinary and Comparative Orthopaedics And Traumatologymentioning
confidence: 73%
“…25 Results of the association of breed with body size showed that maxi and giant dogs had increased risk of having cranial cruciate ligament rupture, as already reported. 2,16,17,26,27,30,38 All dogs affected in groups 2 and 8 weighed more than 35 kg. In this sense, a recent study describes that the prevalence of stifle joint osteoarthritis at the time of cranial cruciate ligament rupture diagnosis was higher in dogs weighing more than 35 kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Pećin et al . 2017). Conversely, the Greyhound, despite also being a large‐breed dog, has a low rate of CCLR, leading to the theory that there is a genetic influence on CCLR predisposition (Witsberger et al .…”
Section: Program Heritability All Dogs (N = 333) Heritability With Sementioning
confidence: 99%